Influence of maternal diet on flavor transfer to amniotic fluid and breast milk and children's responses: a systematic review. (28th March 2019) - Spahn, Joanne M; Callahan, Emily H; Spill, Maureen K; Wong, Yat Ping; Benjamin-Neelon, Sara E; Birch, Leann; Black, Maureen M; Cook, John T; Faith, Myles S; Mennella, Julie A; Casavale, Kellie O
ABSTRACT: Background: Maternal diet during pregnancy and lactation may provide the earliest opportunity to positively influence child food acceptance. Objective: Systematic reviews were completed to examine the relation among maternal diet during pregnancy and lactation, amniotic fluid flavor, breast-milk flavor, and children's food acceptability and overall dietary intake. Design: A literature search was conducted in 10 databases (e.g., PubMed, Embase, Cochrane, and CINAHL) to identify articles published from January 1980 to June 2017. Data from each included study were extracted, risk of bias assessed, evidence synthesized qualitatively, conclusion statements developed, and strength of the evidence graded. Results: Eleven and 15 articles met a priori criteria for inclusion to answer questions related to maternal diet during pregnancy and lactation, respectively. Conclusions: Limited but consistent evidence indicates that flavors (alcohol, anise, carrot, garlic) originating from the maternal diet during pregnancy can transfer to and flavor amniotic fluid, and fetal flavor exposure increases acceptance of similarly flavored foods when re-exposed during infancy and potentially childhood. Moderate evidence indicates that flavors originating from the maternal diet during lactation (alcohol, anise/caraway, carrot, eucalyptus, garlic, mint) transmit to and flavor breast milk in a time-dependent manner. Moderate evidence indicates that infants can detect diet-transmitted flavors in breast milk within hours of a single maternal ingestion (alcohol, garlic, vanilla, carrot), within days after repeated maternal ingestion (garlic, carrot juice), and within 1–4 mo postpartum after repeated maternal ingestion (variety of vegetables including carrot) during lactation. Findings may not generalize to all foods and beverages. Conclusions cannot be drawn to describe the relationship between mothers' diet during either pregnancy or lactation and children's overall dietary intake.